Identifying Inhibiting and Enabling Factors for Design-Build Method Adoption in Local Government Projects in Indonesia - Armaeni, Ni Komang; Triswandana, I Wayan Gde Erick; Sanjaya, I Putu Ari (Universitas Ibn Khaldun Bogor, 2025)
A design and build (DB) is a method that offers several advantages, including accelerated implementation time and reduced costs. Nevertheless, the implementation of the DB method in local government projects in Indonesia is still constrained by a number of factors. The objective of this study is to identify the inhibiting and enabling factors in the adoption of the DB method in local government. This research approach employed a Delphi survey, which involved experts and practitioners. The data was collected through the administration of questionnaires. The study identified 15 key barriers to DB implementation, including a lack of supportive regulations, low literacy in risk management, and a lack of staff knowledge and experience in implementing DB methods. Furthermore, distrust and a preference for more familiar methods represent significant obstacles. In contrast, there were 20 enabling elements, which were divided into four main factors. These were regulatory adjustment, capacity building of users and service providers, effective management, and external support. Regulatory adjustments included adjustments to the DB tendering and contracting system and shared perceptions with the legislature. The capacity building of users and service providers encompasses pilot projects, individuals who possess a comprehensive understanding of DB, and the provision of sufficient financial resources. Effective management encompasses inter-organisational communication and knowledge transfer, as well as DB-related socialisation and training. External support encompasses public acceptance, stakeholder support, and favourable political, economic, and cultural conditions. The findings of this research indicate that in order to enhance the utilisation of the DB method within local government, it is essential to address the identified obstacles and to capitalise on the identified opportunities.